Late Cretaceous phymosomatids and the true identity of Cidarites granulosus Goldfuss, 1829 (Echinoidea, Phymosomatoida) - Schlüter, Nils; Kutscher, Manfred; Smith, Andrew B.; Jagt, John W. M.; Lees, Jackie A. (Zootaxa, 2012)
A revision of Late Cretaceous species of the common regular echinoid genus Phymosoma Haime in d’Archiac & Haime,1853 has revealed that Cidarites granulosus Goldfuss, 1829 has generally been misinterpreted in the literature. The typespecimen of this species is undoubtedly conspecific with material from the lower Maastrichtian of Rügen, northeast Ger-many. What authors have referred to as Phymosoma granulosum in northern temperate (boreal) regions of western Europeand in the Middle East in fact represents an undescribed form which we here name Phymosoma ravni sp. nov., which dif-fers from Cidarites granulosus in having better-developed biserial pore zones adapically, proportionally larger mamelonson primary tubercles, a flush peristome, and stout, non-facetted primary spines. The proper placement of Cidarites granulosus within the family Phymosomatidae Pomel, 1883 is ambiguous; it appears to be most closely related to Phymosoma.